Interplay of strain and interdiffusion in Heusler alloy bilayers. Issue 5 (17th April 2015) - Dutta, Biswanath; Hickel, Tilmann; Neugebauer, Jörg; Behler, Christian; Fähler, Sebastian; Behler, Anna; Waske, Anja; Teichert, Niclas; Schmalhorst, Jan‐Michael; Hütten, Andreas
<x xml:space="preserve">Abstract</x> Combining conventional and inverse magnetocaloric materials promises to enhance solid state refrigeration. As a first step here we present epitaxial Ni–Mn–Ga/Ni–Mn–Sn bilayer films. We examine the dependence of the lateral and normal lattice constants on the deposition sequence by combining experimental and ab initio techniques. Structural properties are determined with X‐ray diffraction as well as highresolution transmission electron microscopy, while ab initio calculations explain the interplay of strain, local relaxations and the interdiffusion of atoms. The latter is confirmed by Auger electron spectroscopy and is expected to have a noticeable impact on the functional properties of the Heusler materials. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim)